Pengaruh Live Streaming dan Brand Ambassador Engagement terhadap Keputusan Pembelian Erigo: Studi Kasus Penggemar Grup Idola Jkt48 terhadap Produk Erigo di Karawang. - Nur Fatihah, Syifa Kamila; Ratnasari, Ina (Masyarakat Ekonomi Syariah Bogor, 2024)
This research study aims to examine the influence of live streaming and brand ambassador of idol group JKT48 on the purchasing decisions of Erigo’s product. On this era of digitalization marketing, brands image increasingly leverage interactive online methods and influential personalities to enchance their target market and lead customer behavior. As such live streaming providing a real time immersive and interactive shopping experience that creates a dynamic engaging platform for product presentation. Brand ambassador with their credibility and relatability that can reach the significantly impact customer perseptions and preferences, further leading purchace decisions. This research employs a quantitative employ with surveying questionnaire sample of JKT48’s fans that bought Erigo product to gather data impact from their engagement and live streaming with factors influence their purchasing decisions.